FATTY ACIDS COMPOSITION AND PHYSICO-CHEMICAL CONSTANTS OF PUNICA GRANATUM L. SEED OIL - Zeynalova, Aydan Mirza gyzy; Novruzov, El’dar Novruz ogly (Химия растительного сырья, 2019)
One of the important sources of essential fatty acids may be products of plant origin, in particular, oils extracted from seeds of wild and cultivated plants. One of these resources is wild-growing Punica granatum. The fatty acid composition of the lipid fractions of the seeds of wild-type pomegranate growing on the territory of Galalti, Siyazan region of the Azerbaijan Republic was assessed by gas chromatography after conversion to the methyl esters of the corresponding fatty acids. The highest oil yield – 12.92% was obtained by the extraction of the seeds at 60 °C for 8 h by Soxhlet extractor. Chromatographic analysis of the fatty oil of pomegranate seeds made it possible to establish the presence of 9 higher fatty acids. The main component of P. granatum seed oil was punicic acid (79.64%). Palmitic and stearic acids were found in small quantities. Content of these fatty acids were 3.29% and 2.43%, respectively. The least amount is accounted for by the share of myristic (0.03%) and heptadecanoic acids (0.03%).The analyses of physico-chemical constants and organoleptic properties of seed oil of P. granatum L. shows that the saponification numbers of wild-type pomegranate was 192.91 that indicates higher solubility of soap in water that can be made from it. The percentage of free fatty acids in our sample was 0.20% and the peroxide value – 3.03. The obtained results allow to consider the seed oil of this plant as good dietary fatty acid source. Thus, this study can provide valuable information for medicine and food industry for the development of drugs and food additives based on Azerbaijan wild-type pomegranate seed oil.